Snapdragons: a house for hedgehog - Harvey, Damian; Elliott, Rebecca (Oxford University Press UK, 2004)
Hedgehog is feeling cold in his house, so he goes out to look for a new one. He visits Otter, Rabbit, squirrel and Mole, but none of their houses are right for him. On his way home, he falls over and rolls downhill. Leaves get stuck on his prickles and these warm him up in his own home